People relaxing on beds outdoors - Unknown:::Creator::::::::::::
Photograph shows three beds possibly on a deck with railings in a wooded area. There is a teenage girl relaxing on the bed on the far left and the feet and legs of another person on the far right bed. It is probably located at the YWCA's Camp Ayun Map in Big Basin.